Assessment of Groundwater Quality of Udayagiri area, Nellore District, Andhra Pradesh, South India Using Multivariate Statistical Techniques (2016)
Hydrogeochemical studies were carried out in and around Udayagiri area of Andhra Pradesh in order to assess the chemistry of the groundwater and to identify the dominant hydrogeochemical processes and mechanisms responsible for the evolution of the chemical composition of the groundwater. Descriptive statistics, correlation matrices, principal component analysis (PCA), together with cluster analysis (CA) were used to gain an understanding of the hydrogeochemical processes in the study area. PCA has identified 4 main processes influencing the groundwater chemistry viz., mineral precipitation and dissolution, seawater intrusion, cation exchange, and carbonate balance. Further, three clusters C1, C2 and C3 were obtained. Samples from C1 contain high level of Cl− and may be due to the intensive evaporation and contamination from landfill leachate. Most of the samples from C2 are located closer to the sea and the high level of Na+ +K+ in these samples may be attributed to seawater intrusion. The geochemistry of water samples in C3 are more likely to originate from rock weathering. This has been supported by Gibbs diagram. The groundwater geochemistry in the study area is mostly of natural origin, but is influenced to some degree by human activity.  Evaluación de la calidad del agua subterránea a través de técnicas estadísticas multivariadas en el área Udayagiri, distrito Nellore, Andhra Pradesh, en el sur de IndiaResumenSe realizaron estudios hidrogeoquímicos en y alrededor del área Udayagiri de Andhra Pradesh para evaluar la química del agua subterránea e identificar los procesos hidrogeoquímicos dominantes y los mecanismos responsables de la evolución en la composición química del agua subterránea. Se utilizaron estadísticas descriptivas, matrices de correlación, análisis de componentes principales, al igual que análisis de grupos, para obtener y entender los procesos hidrogeoquímicos en el área de estudio. Los análisis de componentes principales identificaron cuatro procesos determinantes que influenciaron la química del agua subterránea, estos son, la precipitación y disolución de minerales, l intrusión de agua marina, el intercambio de cationes y el equilibrio de carbonatos. De esta forma se obtuvieron tres grupos, C1, C2, y C3. Las muestras del grupo C1 contienen un alto nivel de Cl- , lo que podría deberse a la intensa evaporación y contaminación de los lixiviados de rellenos sanitarios. Muchas de las muestras del grupo C2 se ubican cerca del mar y el alto nivel de Na++K+ podría atriburise a la intrusión de agua marina. La geoquímica de las muestras de agua en el grupo C3 probablemente se desprende de la meteorización de rocas. El diagrama de Gibbs valida estos resultados. La geoquímica del agua subterránea en el área de estudio es principalmente de origen natural pero también está influenciado por la actividad humana en algún grado.